Study of oxidative stress and C-Reactive protein in type-2 diabetes mellitus - Dalvi, Shubhangi M.; Hathial, Chandrakiran D.; Yeram, Neelam; Nalavade, Mayuri; Patil, Vinayak W. (International Journal of Research in Medical Sciences, 2019)
Background: Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion and insulin action or both. T2DM is associated with chronic low grade inflammation, possibly through a pathway involving a cytokine-mediated acute-phase response to infection and other inflammatory processes. authors aim to study C-reactive protein (CRP) which is an acute-phase reactant produced primarily in the liver hepatocytes. Oxidative stress levels in newly diagnosed T2M patients were analysed with respect to malondialdehyde (MDA) and nitric oxide (NO). Methods: Case-control study comprising of aged-sex matched subjects: newly diagnosed T2DM cases (n=30) and controls (n=30). The serum samples of subjects were analysed for levels of MDA by Buege and Aust method, while NO levels by Cortas and Wakid’s kinetic cadmium reduction method using spectrophotometer. CRP levels were analysed by using turbidimetry. Statistical analysis was done using Mini-tab 17 software with 95% confidence interval. Results: Serum levels of MDA, NO and CRP in newly diagnosed T2DM patients were significantly increased as compared to healthy controls. Conclusions: Authors concluded that the oxidative stress and inflammation plays a pivotal role in the aetiology of hyperglycemia in T2DM. Oxidative stress and inflammatory markers might help prognosis of T2DM in hyperglycemic individuals with the help of which precautionary measure can be taken to reduce the rate of disease progression. Treatment involving anti-oxidant and anti-inflammatory medications might help to rescue vital organs from damage.